La giustizia e i criteri etici per la distribuzione dei vaccini nell’ambito della pandemia Covid-19: linee della discussione bioetica (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The need to vaccinate large numbers of individuals to obtain heard immunity and the scarcity of available vaccines opens up the problem of ethical criteria for defining the priority of distribution both at the macro-allocation and micro-allocation level. There are several theories in the pluralistic context (libertarian, utilitarian, egalitarian, personalist, communitarian theory) applying different concepts of justice and equity between the market and the common good, with concrete implications in the identification of the priority of phases and categories. Vaccine distribution inevitably calls into question also the global dimension of distribution (global justice), as we will never fully emerge from the pandemic if we do not all come out of the pandemic. The voice of ethics plays an essential role in this area both through the recommendations of experts and interdisciplinary committees and through the possible consultation of the citizens.
Keywords: Vaccination; ethics; justice; equity; common good